Fleabrain loves Franny - Rocklin, Joanne. (Amulet Books, 2014)
"This middle-grade novel takes place in Pittsburgh in 1952-53. The protagonist is Franny, a young girl of imagination, curiosity, and stubbornness. While recovering from polio, she begins a correspondence with a flea named Fleabrain"--